Emotional intelligence of students with different degrees of involvement in electronic social networks - Fofanova, Galina A.; Pozdnyakova, Alyaksandra V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article defines the concept of involvement in electronic social networks (ESN), the technique of identifying the degree of involvement in the ESN, analyzes and describes the features of emotional intelligence of students with varying degrees of involvement in the ESN. It was found that the users with a higher degree of involvement in the ESN have a lower level of emotional intelligence than the users with a less expressed degree of involvement in the ESN. It was also found that people with a higher degree of involvement in the ESN are less able to control their emotional state and expression and less able to influence the emotional state of other people. However, users with a higher degree of involvement in the ESN have a higher level of understanding of their own emotions and emotions of other people.
Keywords: involvement; Internet addiction; motives of affiliation; electronic social networks; students; emotions; emotional intelligence